THE ROLE OF PUBLIC RELATIONS IN HIGHER EDUCATION DEVELOPMENT - Muslihuddin, Muslihuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public Relations (Public Relations) has a strategic role in developing higher education in the era of global competition. This article aims to examine the contribution of Public Relations in building an institutional image, increasing the attraction of new students, managing relationships with stakeholders, handling crisis management, and supporting internationalization. The research uses qualitative methods with a descriptive approach through literature analysis. The results show that Public Relations is able to strengthen the reputation of institutions and the competitiveness of higher education through effective communication strategies and collaboration with various parties. These findings emphasize the importance of adequate resource allocation to support the strategic function of Public Relations in achieving the vision and mission of higher education.